2012
DOI: 10.1590/s0366-69132012000300015
|View full text |Cite
|
Sign up to set email alerts
|

Physical chemistry research of a concrete dam with over 50 years of operation

Abstract: Guaricana hydroelectric power plant concrete dam, located in the South of Brazil, was investigated after 49 years of operation. A part of the mortar was altered to ettringite, and other by-products. The inner defects in the fracture and polished sample surfaces were detected by CT and SEM. The samples were extracted from two parts of the dam from top to valley. Elemental chemical composition and phases were determined by EDS and XRD analysis. The reservoir water showed that it was less aggressive to the concre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The drilled core method is one of the most common methods because the inside of the concrete could be revealed and exposed directly by this method. Moreover, the concrete core could be used as the samples of laboratory tests [14]. Some other methods, including indentation method, rebound method, and ultrasonic method, are also applied to the dam concrete degradation examination [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drilled core method is one of the most common methods because the inside of the concrete could be revealed and exposed directly by this method. Moreover, the concrete core could be used as the samples of laboratory tests [14]. Some other methods, including indentation method, rebound method, and ultrasonic method, are also applied to the dam concrete degradation examination [15].…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [19] have shown that the concrete of Yongan Dam is deteriorated due to the thaumasite form of sulphate attack, according to microanalytical investigations, SEM and energy disperse Xray (EDX). Portella et al [14] analyzed the elemental chemical composition and phases of a concrete dam with over 50 years of operation by EDS and XRD techniques. However, most of the microanalytical studies on the dam concrete degradation are based on single or two experimental techniques, which might cause the local uncertainty of the precipitations.…”
Section: Introductionmentioning
confidence: 99%